Enhancing agricultural resilience in Uzbekistan through farmers’ decisionmaking autonomy - Djanibekov, Nodir; Takeshima, Hiroyuki; Mirkasimov, Bakhrom; Akramov, Kamiljon T. (Center For Policy Research and Outreach, 2025)
KEY MESSAGE • Greater farmer’s decision-making autonomy enhances resilience in technical efficiency during economic shocks. • Technical efficiency improves with autonomy, as farmers can adjust resource use, sustain productivity, and make adaptive choices regarding crop selection and input management. • Eliminating top-down land allocations, granting secure land use rights, expanding financial and market access, and decentralizing training programs can improve the capacity of farmers to become more productive and adaptable in the face of current and future challenges.